B-type allatostatin modulates immune response in hepatopancreas of the mud crab Scylla paramamosain. (September 2020) - Xu, Zhanning; Wei, Yujie; Guo, Songlin; Lin, Dongdong; Ye, Haihui
Abstract: B-type allatostatin (AST-B) is a pleiotropic neuropeptide, widely found in arthropods. However, the information about its immune effect in crustaceans is unknown. In this study, we identified the nervous tissue as the main site for Sp-AST-B expression, while its receptor gene ( Sp-AST-BR ) is widely expressed in various tissues, including the hepatopancreas. This suggests the peptide's potential role in diverse physiological processes in the mud crab Scylla paramamosain . In situ hybridization revealed that Sp-AST-BR is mainly localized in the F-cell of hepatopancreas. Furthermore, we found a significant up-regulation of Sp-AST-BR transcripts in the hepatopancreas following exposure to lipopolysaccharide (LPS) or polyriboinosinic polyribocytidylic acid (Poly (I:C)). Results from in vitro and in vivo experiments revealed that treatment with a synthetic AST-B peptide mediated significant upregulation in expression of AST-BR, nuclear factor-κB (NF-κB) pathway components (Dorsal and Relish), pro-inflammatory cytokine (IL-16) and antimicrobial peptides (AMPs) in the hepatopancreas. In addition, AST-B treatment mediated significant elevation of nitric oxide (NO) production and enhanced the bacteriostasis capacity of the hepatopancreas tissue in vitro . Taken together, these findings reveal the existence of a basic neuroendocrine-immune (NEI) network in crabs, and indicate that AST-B could couple with its receptor to trigger downstream signaling pathways and induce immune responses in the hepatopancreas. Highlights: Sp - AST-BR expression induced by LPS and Poly (I:C) challenges. Sp -AST-B modulated the NF-κB signaling, pro-inflammatory cytokine and AMPs expression both in vitro and in vivo. Sp -AST-B enhanced the concentration of nitric oxide and the bacteriostasis of crabs in vitro.